KUPU-KUPU (LEPIDOPTERA) DARI AIR TERJUN BUKIT GATAN KECAMATAN STL ULU TERAWAS KABUPATEN MUSI RAWAS PROVINSI SUMATERA SELATAN - Anis Lestari; Harmoko Harmoko; Ivoni Susanti (Biotik, 2020)
This study aims to determine the type of butterfly (Lepidoptera) in Bukit Gatan Waterfall, STL Ulu Terawas District, Musi Rawas Regency. Inventory is an activity carried out by data collection, observation, recording and compilation of data to be analyzed, both in the form of data and goods. Data collection techniques such as observation, interviews and documentation of butterfly types. Inventory data analysis techniques using qualitative descriptive techniques. Butterflies are divided into six families namely Nymphalidae, Hesperiidae, Papilionidae, Riodinidae, Lycaenidae and Pieridae families. The butterflies obtained were collected by direct capture carried out by cruising techniques and then identified based on the species and their respective families.